A Dual Luciferase Reporter System for B. burgdorferi Measures Transcriptional Activity during Tick-Pathogen Interactions - Adams, Philip P.; Flores Avile, Carlos; Jewett, Mollie W. (Frontiers in Cellular and Infection Microbiology, 2017)
Knowledge of the transcriptional responses of vector-borne pathogens at the vector-pathogen interface is critical for understanding disease transmission. Borrelia (Borreliella) burgdorferi, the causative agent of Lyme disease in the United States, is transmitted by the bite of infected Ixodes sp. ticks. It is known that B. burgdorferi has altered patterns of gene expression during tick acquisition, persistence and transmission. Recently, we and others have discovered in vitro expression of putative non-coding RNAs found internal, overlapping, and antisense to annotated open reading frames in the B. burgdorferi genome. However, there is a lack of molecular genetic tools for B. burgdorferi for quantitative, strand-specific, comparative analysis of these transcripts in distinct environments such as the arthropod vector. To address this need, we have developed a dual luciferase reporter system to quantify B. burgdorferi promoter activities in a strand-specific manner. We demonstrate that constitutive expression of a B. burgdorferi codon-optimized Renilla reniformis luciferase gene (rlucBb) allows normalization of the activity of a promoter of interest when fused to the B. burgdorferi codon-optimized Photinus pyralis luciferase gene (flucBb) on the same plasmid. Using the well characterized, differentially regulated, promoters for flagellin (flaBp), outer surface protein A (ospAp) and outer surface protein C (ospCp), we document the efficacy of the dual luciferase system for quantitation of promoter activities during in vitro growth and in infected ticks. Cumulatively, the dual luciferase method outlined herein is the first dual reporter system for B. burgdorferi, providing a novel and highly versatile approach for strand-specific molecular genetic analyses.